2020
DOI: 10.15171/jlms.2020.02
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of The Effects of Clobetasol 0.05% and Photodynamic Therapy Using Aminolevulinic Acid With Red Light in the Treatment of Severe Nail Psoriasis

Abstract: Introduction: The treatment of nail psoriasis is often difficult and unsatisfactory due to therapy resistance. This study aimed to compare the efficacy of clobetasol 0.05% ointment and photodynamic therapy (PDT) using aminolevulinic acid (ALA) and red light in the treatment of severe nail psoriasis. Methods: This open-trial study included 69 nails of 8 patients with severe nail psoriasis. Thirty-four nails were treated with clobetasol 0.05% ointment and 35 nails were treated with ALA-PDT. ALAPDT treatment was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…There was a significant time-effect improvement in all the nail matrix, nail bed, and total NAPSI scores in both treatment groups. Although more data are needed for further evidence, these initial results suggest that the efficacy of ALA-PDT at a 24-week follow-up was greater than that of clobetasol [ 36 ].…”
Section: Efficacy Of Ala-pdt Therapymentioning
confidence: 99%
“…There was a significant time-effect improvement in all the nail matrix, nail bed, and total NAPSI scores in both treatment groups. Although more data are needed for further evidence, these initial results suggest that the efficacy of ALA-PDT at a 24-week follow-up was greater than that of clobetasol [ 36 ].…”
Section: Efficacy Of Ala-pdt Therapymentioning
confidence: 99%
“… Phase III clinical trial accomplished [ 128 , 131 ] 500 patients with plaque psoriasis Randomized double-blind parallel control ALA-PDT 35 patients with fingernails psoriasis Randomized double-blind parallel control The clinical symptoms of patients were relieved, and ALA-PDA had obvious advantages in the treatment of severe psoriasis. Small sample clinical trials [130] 311 nm narrow band UVB phototherapy 22 patients with plaque psoriasis Randomized double-blind parallel control Oxidative stress-related parameters were significantly improved in the patients and their quality of life was improved. Small sample clinical trials [129] …”
Section: Clinical Applications Of Ros In the Treatment Of Psoriasismentioning
confidence: 99%
“…In recent years, phototherapy has been favored by clinical research. In 2020, in a randomized, double-blind experiment involving 35 fingernail Ps patients, it was found that the aggregation of ROS caused by ALA-PDT induced the apoptosis of keratinocytes and ameliorated the clinical symptoms of patients, which was well tolerated [130] . It has obvious advantages compared with clobetasol propionate in treating severe Ps.…”
Section: Clinical Applications Of Ros In the Treatment Of Psoriasismentioning
confidence: 99%
“…Psoriatic nail disease (PND) affects more than 50% of cutaneous psoriasis and 80% psoriatic arthritis patients and is considered a difficult‐to‐treat condition 1,2 . In the past 20 years, 31 clinical trials on topical treatment of PND have been conducted (Table 1), with corticosteroids ( n = 16, clobetasol, betamethasone) and Vitamin D derivatives ( n = 13, calcipotriol, tacalcitol) remaining the most studied agents 3–33 . Products containing both calcipotriol and betamethasone dipropionate (Cal/BD) are highly effective against psoriasis and have become available as a hypersaturated aerosol foam.…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 2 In the past 20 years, 31 clinical trials on topical treatment of PND have been conducted (Table 1 ), with corticosteroids ( n = 16, clobetasol, betamethasone) and Vitamin D derivatives ( n = 13, calcipotriol, tacalcitol) remaining the most studied agents. 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 Products containing both calcipotriol and betamethasone dipropionate (Cal/BD) are highly effective against psoriasis and have become available as a hypersaturated aerosol foam. In addition to superior efficacy in treating skin lesions, results of a 12‐week randomized controlled trial (RCT) on Cal/BD foam for PND on fingernails showed a 44% decrease of clinical symptoms with only minor side effects.…”
Section: Introductionmentioning
confidence: 99%